Glyptothorax mibangi, a new species of catfish (Teleostei: Sisoridae) from the Tisa River, Arunachal Pradesh, northeast India - Darshan, Achom; Dutta, Rashmi; Kachari, Akash; Gogoi, Budhin; Das, Debangshu Narayan (Zootaxa, 2015)
Glyptothorax mibangi, a new sisorid catfish, is described from the Tisa River of Arunachal Pradesh, India. The new species can be distinguished from its congeners in the Ganga–Brahmaputra and Barak–Surma–Meghna basins by the following combination of characters: an obtuse leaf-shaped thoracic adhesive apparatus with a spindle-shaped median depression, skin ridges present over the entire apparatus including the depressed region; ventral surface of pectoral spine and first pelvic-fin ray non-plaited; slender body with depth of 10.4–13.5% SL; caudal peduncle shallow with depth 6.8–8.3% SL; snout long with length 52.9–58.6% HL; and 2+7 gill rakers on the first branchial arch.